Behavioral complexity and its impact on the quality of work life: An exploratory study in a sample of Iraqi 5 Stars class hotels - Amira Hammoud Hassan (Peerian Journals Publishing, 2024)
The research aims to direct the attention of hotel departments to the importance of working towards providing an organizational climate that pushes towards providing the best performance of working individuals through the industry of a professional life that is characterized by stability and bypassing cases and indicators of behavioral complexity that may cast a shadow on the nature of the decisions taken. The research problem was represented by a case The emerging conflict between the overall behavioral complexities and the creation of sound working conditions that raise the curve of the quality of work life in Iraqi hotel organizations. The research sample included (109) respondents in a group of premium class hotels in the city of Baghdad. The most prominent results are that the opinions of the sample place the reality of hotel work and its various adoptions in a location far from the principle of stability and job security, which is due to the state of economic instability in Iraq as a whole and the state of structural imbalance in this economy, which has always been subject to successive crises at all levels, and therefore hotel organizations It is exposed to the effects of these crises and imbalances, while the most prominent recommendations are the inevitability of cultivating a greater level of awareness. R with job security and the consolidation of the central idea in the psyche of individuals, which is summed up that the hotel management is a support for the working individual and therefore is determined to overcome any crisis or abnormal circumstance without prejudice to the job of individuals and to move away from the approach of forced layoffs of individuals or issuing instructions that would cause damage to life professional for individuals
Keywords: behavioral complexity; quality of work life; Iraqi 5 Stars class hotels